(untitled) (Baghdad Science Journal, 2023)
In this study, the upgrading of Iraqi heavy crude oil was achieved utilizing the solvent deasphalting approach (SDA) and enhanced solvent deasphalting (e-SDA) by adding Nanosilica (NS). The NS was synthesized from local sand. The XRD result, referred to as the amorphous phase, has a wide peak at 2Θ= (22 - 23º) The inclusion of hydrogen-bonded silanol groups (Si–O–H) and siloxane groups (Si–O–Si) in the FTIR spectra. The SDA process was handled using n-pentane solvent at various solvent to oil ratios (SOR) (4-16/1ml/g), room and reflux temperature, and 0.5 h mixing time. In the e-SDA process, various fractions of the NS (1–7 wt.%) have been utilized with 61 nm particle size and 560.86 m²/g surface area in the presence of 12 ml/g SOR with 0.5 hr. mixing time at room and reflux temperature. The results showed that heavy crude was upgraded maximally using 7 wt.% of NS. The API increased to 35.9, while the asphaltene reduction increased to 87.22%. The removal of sulfur, vanadium, and nickel increased to 51.17%, 55.07%, and 69.87%, respectively.